A Database for the Future - Sören Edvinsson; Elisabeth Engberg (Historical Life Course Studies)
The Demographic Data Base (DDB) at the Centre for Demographic and Ageing Research (CEDAR) at Umeå University has since the 1970s been building longitudinal population databases and disseminating data for research. The databases were built to serve as national research infrastructures, useful for addressing an indefinite number of research questions within a broad range of scientific fields, and open to all academic researchers who wanted to use the data. A countless number of customised datasets have been prepared and distributed to researchers in Sweden and abroad and to date, the research has resulted in more than a thousand published scientific reports, books, and articles within a broad range of academic fields. While there has long been a clear predominance of research within the humanities and social sciences, it has always been used for research in other fields as well, for example medicine. In this article, we first give a brief presentation of the DDB and its history, characteristics, and development from the 1970s to the present. It includes an overview of the research based on the DDB databases, with a focus on the databases POPUM and POPLINK with individual-level data. A number of major traits of the research from 1973 to now have been outlined, showing the breadth of the research and highlighting some major contributions, with a focus on work that would have been very difficult to perform without data from the DDB.